Language As A Barrier In Health Care Communication-A Comparative Study On Rural And Urban Hospitals (Journal of Pharmaceutical Negative Results, 2023)
Communication is the key tool to success. When it comes to healthcare communication, there is a vast gap between medical professionals and patients especially people with a lesser education and people belonging to rural areas. Communication is very much essential in providing quality medical care and content to patients. The effect of the languages and the scientific terms used by medical professionals becomes difficult for the common audience to understand; hence, the understanding gap also increases. This study demonstrates how language becomes a hurdle in healthcare communication depending on the location or locality of the hospital. The main objective of this research paper is to find how language becomes a barrier in health communication depending on the location of the hospital and the communication challenges experienced by rural and urban audiences in hospitals. It will also focus on how infographic designs can help the audience in reducing the communication gap in understanding healthcare information. We have collected 300 samples from 20 different hospitals from both Rural & Urban areas of Jaipur-I City, Rajasthan India. The paper also highlights some of the challenges posed by the language barrier and recommends a few suggestions. This research finding indicates that the language barrier in health communication can be minimized with the use of infographic designs for communication with the audience.